2019
DOI: 10.1111/vde.12771
|View full text |Cite
|
Sign up to set email alerts
|

Progenitor cells expressing nestin, a neural crest stem cell marker, differentiate into outer root sheath keratinocytes

Abstract: Background -Nestin, which was originally described as a neural crest stem cell marker, is known to be expressed in bulge follicle cells of human, canine and murine anagen hairs. However, the capacity of nestin-expressing cells to differentiate into the components of the hair follicle or the epidermis has been insufficiently investigated.Hypothesis/objectives -To determine whether nestin-expressing cells are capable of differentiating into keratinocytes.Animals/materials -A double-transgenic mouse line Nes-Cre/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…Therefore, bone lesions may display unique histological changes in the jawbones. Craniofacial bone development is different from long bones and that it develops from neural crest [27] , [13] , [10] , [28] , [29] . This difference may also be effective in immunostaining results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, bone lesions may display unique histological changes in the jawbones. Craniofacial bone development is different from long bones and that it develops from neural crest [27] , [13] , [10] , [28] , [29] . This difference may also be effective in immunostaining results.…”
Section: Discussionmentioning
confidence: 99%
“…Nestin is a class VI intermediate filament protein; it is known as a specific marker of neural or neural crest stem cells [10] , [13] , [27] , [28] , [29] . Nestin, which tends to be more strongly expressed in mandibular bone morphogenetic stem cells (R).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Nes-Cre/CAG-CAT-EGFP mouse line [24] was generated by crossing CAG-CAT-EGFP mice (courtesy of Junichi Miyazaki, Osaka University, Japan), in which the chloramphenicol acetyltransferase (CAT) gene is anked by two loxP sites [14], with Nes-Cre mice (courtesy of Ryoichiro Kageyama, Kyoto University, Japan) [9]; both mouse strains have a C57BL/6 background. The Nes-CreERT2/CAG-CAT-EGFP mouse line was generated by crossing CAG-CAT-EGFP mice with Nes-CreERT2 mice (courtesies of Itaru Imayoshi and Ryoichiro Kageyama, Kyoto University, Japan), which harbor the CreERT2 gene downstream of the nestin promoter and also have a C57BL/6 background.…”
Section: Micementioning
confidence: 99%
“…Moreover, studies using nestin-driven green uorescent protein (ND-GFP) transgenic mice revealed that ND-GFP cells in the upper HF are multipotent, as they can differentiate into cell lineages with characteristics of neural cells, glial cells, muscle cells, melanocytes, and keratinocytes in vitro [2][3][4][5]18]. Previously, we reported that ORS keratinocytes of adult mice are the descendants of nestin-expressing cells, despite being an epithelial cell lineage [24]. This study aimed to de ne the exact stage when nestin-expression ORS stem/precursor cells appear during HF morphogenesis.…”
Section: Introductionmentioning
confidence: 99%